INIMUNOPATHOLOGIC RELATION BETWEEN Nocardia asteroides AND Brucella abortus t GAINED EXPERIMIENTALLY - Alwan, M. J. (The Iraqi Journal of Veterinary Medicine, 2002)
In order to demonstrated the pathologic changes and immune response of Brucella aboruls strain 19. Vaccinated guinea pigs were experimentally infected With Nocardia asteroides, 24 guinea pigs of both six were divided into four equal groups. The first group was inoculated sub-cutaneously with Brucella abortus strain 19 vaccine. The second group was inoculated inuapulmonary with 1 X 103 C.F.U of viable Nocardia asteroides. Thirty days post-inoculation the first, second and third groups were challenged intrapulmonary with 2.5 K 109 C.F.U. of Nocardia asteroides, the last group served as control. The results showed that mortality was 100 % in non~ vaccinated -animals, 33.4 % in immunized animals with Nocardia asteroides and zero in Brucella abortus vaccinated animals.